Exploring the Critical Relationship Between Virtual and Bedside Nurses - Melanie Chopra (SAGE Open Nursing)
The COVID-19 pandemic has magnified the challenges faced by healthcare professionals; in particular, it exposed the highly stressful work environment the bedside nurse (BSRN) navigates while providing patient care. In response, virtual nursing (VNG) became an innovative solution to fill the gaps in healthcare delivery, and it continues to grow as a nursing discipline. The adoption of VNG, which facilitates real-time communication with BSRNs, presents challenges in maintaining trust and collaboration in a digital environment between the remote virtual nurse (RVN) and the BSRN. Barriers such as skepticism, misperceptions about the RVNs' role, and mistrust are discussed, alongside strategies to improve the working partnership between RVNs and BSRNs. The importance of gaining bedside leadership support, offering mentorship, offloading work from the BSRN, communication techniques, and practical interventions is suggested as potential steps the RVN can take to enhance their collaboration with the BSRN. This article proposes continued integration of VNG throughout diverse healthcare settings to potentially improve patient outcomes and expresses the urgent need for further research to improve the evolving RVN–BSRN partnership.